Carbapenem-Resistant Pseudomonas aeruginosa Strains-Distribution of the Essential Enzymatic Virulence Factors Genes - Tomasz Bogiel; Małgorzata Prażyńska; Joanna Kwiecińska-Piróg; Agnieszka Mikucka; Eugenia Gospodarek-Komkowska (MDPI AG, 2020)
Pseudomonas aeruginosa is one of the most commonly isolated bacteria from clinical specimens, with increasing isolation frequency in nosocomial infections. Herein, we investigated whether antimicrobial-resistant P. aeruginosa strains, e.g., metallo-beta-lactamase (MBL)-producing isolates, may possess a reduced number of virulence genes, resulting from appropriate genome management to adapt to a changing hospital environment. Hospital conditions, such as selective pressure, may lead to the replacement of virulence genes by antimicrobial resistance genes that are crucial to survive under current conditions. The study aimed to compare, using PCR, the frequency of the chosen enzymatic virulence factor genes (alkaline protease-aprA, elastase B-lasB, neuraminidases-nan1 and nan2, and both variants of phospholipase C-plcH and plcN) to MBL distribution among 107 non-duplicated carbapenem-resistant P. aeruginosa isolates. The gene encoding alkaline protease was noted with the highest frequency (100%), while the neuraminidase-1 gene was observed in 37.4% of the examined strains. The difference in lasB and nan1 prevalence amongst the MBL-positive and MBL-negative strains, was statistically significant. Although P. aeruginosa virulence is generally more likely determined by the complex regulation of the virulence gene expression, herein, we found differences in the prevalence of various virulence genes in MBL-producers.